Pengaruh Tingkat Kecemasan Pada Pasien Lansia Dengan Gangguan Hipertensi Di Wilayah Kerja UPTD Puskesmas Cabenge Kabupaten Soppeng - Nur Asiah; ALfina ALfina (Journal on Education, 2025)
Hypertension or High Blood Pressure.Hypertension, or high blood pressure, is defined as an increase in systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg measured on two occasions with a 5-minute interval in a rested or calm condition. Hypertension is more common in the elderly due to the hardening of blood vessels and the heart pumping more forcefully. Additionally, unresolved illnesses can cause excessive anxiety, fear, and stress among the elderly. Consequently, uncontrolled hypertension may lead to various complications To investigate the influence of anxiety levels in elderly patients with hypertension in the working area of UPTD Puskesmas Cabenge, Soppeng Regency.This study employed a case study design with a qualitative descriptive approach. It systematically, factually, and accurately explained the problems in the case study regarding the implementation of anxiety levels in elderly patients with hypertension in the working area of UPTD Puskesmas Cabenge, Soppeng Regency.The expected outcome focuses on providing procedures to enhance comfort through deep breathing relaxation techniques.Conclusion:The action to address anxiety levels in elderly patients with hypertension involves non-pharmacological therapy. Among the effective nursing therapies is the deep breathing relaxation technique, which can reduce blood pressure. This study aims to produce publications in nationally accredited journals and submit to international journals to contribute to nursing science. It also aims to motivate and enhance the knowledge of the elderly regarding hypertension management.